НАЎАЙЫ ЎӘЛАЯТЫ ИЙТ CANIS LUPUS FAMILIARIS ЛЕРИ ЦЕСТОДА КЛАСЫ ГЕЛЬМИНТЛЕРИНИҢ ЗАМАНАГӨЙ ТҮР ҚУРАМЫ - Абдураҳмонов, Ш.А.; Бердибаев, А.С. (FAN va JAMIYAT, 2024)
The article describes the results of helminthological studies conducted on stray and domestic dogs in rural and urban conditions of the Navoi region. Information about the habitats of helminth species, development cycle, and intermediate hosts is also provided.